Correlation between computerised and standard cognitive testing in people with HIV and HIV-negative individuals. Issue 10 (3rd October 2021) - De Francesco, Davide; Underwood, Jonathan; Anderson, Jane; Boffito, Marta; Post, Frank A.; Sachikonye, Memory; Mallon, Patrick W.G.; Haddow, Lewis; Vera, Jaime H.; Kunisaki, Ken M.; Sabin, Caroline A.; Winston, Alan
ABSTRACT: We investigated the correlations and agreement between cognitive assessments made using a computerised (CogState™, six domains) and a standard pen-and-paper battery (five domains) in PWH and lifestyle-similar HIV-negative individuals. Demographically adjusted domain and global T -scores were obtained and used to define cognitive impairment according to the multivariate normative comparison (MNC) criteria. Correlations between T -scores and the agreement between the classifications of cognitive impairment obtained from the two batteries were assessed using the Spearman's rank correlation and Cohen's κ, respectively. The correlation between global T -scores from the two batteries was 0.52 (95% CI 0.44–0.60) in PWH and 0.45 (0.29–0.59) in controls ( p  =   0.38 for their difference). Correlations were generally stronger between domains within the same battery than between those from different batteries. The agreement between the two batteries in classifying individuals as cognitively impaired or not impaired was fair in PWH ( κ  =   0.24) and poor in HIV-negative individuals ( κ  =   −0.02). The moderate correlation between overall cognitive function and the modest agreement between binary classifications of cognitive impairment obtained from two different batteries indicate the two batteries may assess slightly different components of cognition.